Inventory of insect pests in Edamame soybean plant in Kebonsari, Jember - Trisnani Alif; Ema Dwi Martina; Iqbal Erdianysah; Andarula Galushati (KHD Production, 2025)
Edamame, Glycine max (L.) Merrill, a high-value commodity with significant economic potential in Indonesia both domestic and international markets. One of the main issues limiting the productivity of edamame soybean plants is attacked by plant pests. This was field experiment aimed at an inventory of important pest on edamame soybean plant in Kebonsari Jember. This research was conducted on edamame soybean cultivation in Kebonsari village, Sumbesari District, Jember, East java. The method used is a purpose survey at a specific sample point. A sampling of insect pest is done by direct observation, yellow traps, sweep nets and pitfall traps. The pests found were put in a killing bottle or 70% alcohol, collected and identified. The pests identified on edamame soybean plants are grasshoppers, whiteflies, armyworms, and leaf-rolling caterpillars and include on the five ordos are Hemiptera, Coleoptera, Diptera, Orthoptera, and Thysanoptera.